A CONSORT-compliant prospective randomized controlled trial: radiation dose reducing in computed tomography using an additional lateral scout view combined with automatic tube current modulation. Issue 30 (July 2017) - Peng, Wanlin; Li, Zhenlin; Xia, Chunchao; Guo, Yingkun; Zhang, Jinge; Zhang, Kai; Li, Lei; Zhao, Fei
Abstract: Background: Radiation exposure has been a hot point in research field of computed tomography (CT). Recently, automated tube current modulation (ATCM) has emerged as an important technique to reduce radiation exposure. Many studies have shown that the difference in scout view would affect modulation. This prospective randomized controlled study is aimed to investigate the impact of an additional lateral scout view on radiation dose and image quality in CT using ACTM. Methods: Combined with ATCM (Care Dose 4D) on multidetector CT, 2 thoracic phantom CT image series were acquired in which planning was conducted with either an anteroposterior (AP) or an AP-lateral scout view. Also, 410 patients underwent thoracic CT examinations using Care Dose 4D modulation and were randomized to either a scan planned with an AP-lateral scout or a single AP scout. Effects of the different scout views on applied effective milliampere seconds (mAs), volume CT dose index (CTDIvol) and dose–length–product (DLP) were analyzed. The quality of patient CT images was also assessed. Data were analyzed using independent t tests and linear correlation analysis. Results: Compared with AP groups, the mean CTDIvol (phantom, 0.89 ± 0.08 vs 1.36 ± 0.26 mGy, P  < .001; in patients, 1.12 [0.96, 1.34] vs 2.16 [1.66, 2.64] mGy, P  < .001) and DLP (in phantom, 26 [23.25, 28] vs 40 [34.25, 48] mGy×cm, P  < .001; in patients, 41 [33, 41] vs 77 [60.5, 99.5] mGy×cm, P  < .001) were significantly reduced by approximately 50% in AP-lateral scout view group. With the AP-lateral topogram, the radiation dose on different off-center positions was essentially equal (CTDIvol: 0.76–0.99 mGy; DLP: 22–28 mGy×cm effective dose: 0.31–0. 39 mSv). For image quality, contrast-to-noise ratio and signal-to-noise ratio values in the AP group were similar to those of AP-lateral scout view group. Conclusion: AP combined with an additional lateral scout view using ACTM can significantly reduce the radiation dose without compromising image quality in chest screening CT.